INVESTIGATION ON WETTING PATTERN OF NORMAL AND SURGE IRRIGATION FOR VARIATION OF SOIL TYPES - Aziz, Nur Atiqrah (Universiti Teknologi PETRONAS, 2017)
Infiltration and irrigation plays an important role in connecting the relationship between soil and water. To come out with the best soil to use for the canal to supply water to the plant, that can gives adequate infiltration rate, optimum water retained and also can withstand surge and normal irrigation, this study was executed. Preliminary study was done to know the soil classification for six types of soil which are topsoil, sand, soil from corn farm, soil vegetable farm, soil from palm oil farm and peat soil. As for the soil classifications, it includes the moisture content, specific gravity, bulk density, porosity, permeability and particle size distribution. The soil classification result showed that the topsoil is the sandy clay, sand is purely sand, soil from corn farm, vegetable farm and palm oil farm is sandy loam and peat soil is sandy gravel.